Concepções políticas e educacionais de Renato Jardim na década de 1930 - Cunha, Marcus Vinicius da; Silva, Tatiane da [UNESP] (My University, 2013)
This article aims to analyze the political and educational conceptions of Renato Jardim, intellectual who participated actively in Brazilian educational and political scenario in the early decades of XXth century. He was responsible for educational reform initiatives and had an active participation in major debates on education that occurred at that time. The methodology is the traditional analyses of bibliography. In addition to literature specialized in this theme, this work uses the author’s autobiography published in 1946 and four books of his own published between 1932 and 1936. In political area, it examines his arguments concerning the government stated by Getúlio Vargas in 1930 and the constitutionalist movement of 1932. In educational area, the work analyses his ideas regarding the introduction of psychoanalysis in pedagogical practices and his thoughts in search of a definition for the concept of New School.

Este artigo tem por objetivo analisar as concepções políticas e educacionais de Renato Jardim, intelectual que participou ativamente na cena educacional e política brasileira nas primeiras décadas do século XX, tendo sido responsável por iniciativas de reforma educacional e ativo participante nos mais importantes debates sobre a educação ocorridos na época. A metodologia empregada é a análise bibliográfica em moldes tradicionais, utilizando, além de literatura especializada no tema, a autobiografia do autor publicada em 1946 e quatro livros de sua autoria publicados entre 1932 e 1936. No campo político, são examinados os argumentos do autor relativos ao governo de Getúlio Vargas instituído em 1930 e ao movimento constitucionalista de 1932. No campo da educação, o trabalho analisa as ideias do autor a respeito da introdução da psicanálise nas práticas pedagógicas e as suas reflexões em busca de uma definição para o conceito de Escola Nova.
Renato Jardim’s political and educacional ideas in the decade of 1930
Keywords: Renato Jardim; Biography; Brazilian Education; New School; Psychoanalysis; Renato Jardim; Biografia; Educação Brasileira; Escola Nova; Psicanálise